2015
DOI: 10.1111/hex.12368
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to shared decision making in mental health care: qualitative study of the Joint Crisis Plan for psychosis

Abstract: Background Despite increasing calls for shared decision making (SDM), the precise mechanisms for its attainment are unclear. Sharing decisions in mental health care may be especially complex. Fluctuations in service user capacity and significant power differences are particular barriers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
109
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(113 citation statements)
references
References 33 publications
2
109
1
1
Order By: Relevance
“…There are clear indications within the participants' accounts that articulation of dissociative experiences and needs is Insights into Dissociative Identity Disorder 15 particularly difficult during periods of exacerbated distress, which further indicate the need for preventive planning and informed psychological support (Lloyd, 2015). Similar results around barriers to service user led care plans have been found elsewhere in the psychosis literature, with clinician apathy, misunderstanding as to the level of engagement required to recognise service user choices, and poor collaboration being key to undermining the process (Farrelly, et al, 2016). The participants of the current study reported struggling to find a balance in power with many ward staff that would have helped facilitate collaborative care…”
supporting
confidence: 59%
“…There are clear indications within the participants' accounts that articulation of dissociative experiences and needs is Insights into Dissociative Identity Disorder 15 particularly difficult during periods of exacerbated distress, which further indicate the need for preventive planning and informed psychological support (Lloyd, 2015). Similar results around barriers to service user led care plans have been found elsewhere in the psychosis literature, with clinician apathy, misunderstanding as to the level of engagement required to recognise service user choices, and poor collaboration being key to undermining the process (Farrelly, et al, 2016). The participants of the current study reported struggling to find a balance in power with many ward staff that would have helped facilitate collaborative care…”
supporting
confidence: 59%
“…Another barrier to SDM in mental health care is a lack of trust in patients' ability to fully participate in the decision‐making process. Qualitative studies with clinicians have found that they often express concern that patients will not make optimal treatment decisions . This may be due, in part, to doubts that patients will select evidence‐based treatments (EBTs) that are recommended for their presenting concerns.…”
Section: Barriers To Sdm In Mental Health Carementioning
confidence: 99%
“…Furthermore, it is also unknown how PBSPs, which are informed by a potentially novel model of care (PBS), might be perceived by mental health nurses who are key in care planning and delivering physical interventions (Stubbs, Leadbetter, & Paterson, ). The importance of attitudes in managing challenging situations and in reducing restrictive interventions such as restraint has been acknowledged (NHS Protect, ; RCN, ), and nurses' attitudes have been found to impact on the delivery of a range of interventions (Bee, Price, Baker, & Lovell, ; Farrelly et al, ; Price, Baker, Bee, & Lovell, ). Understanding mental health nurses' attitudes to the use of PBSPs will therefore be important in determining whether and how they can be implemented in practice.…”
Section: Introductionmentioning
confidence: 99%